IMPROVING STUDENTS’ MOTIVATION IN SPEAKING BY USING ROLE PLAY IN VIDEO MODELLED CONVERSATION (VMC) - Husin, Sy.; Supardi, Iwan; ., Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : Role play in Video Modelled Conversation are proposed in the teaching of speaking not only because of their appealing forms but also due to their salient features, as multimedia to improve the students? motivation in speaking. This study investigated students? motivation by using Dornyei?s framework of language learning motivation. A questionnaire and a semi-structured interview were also employed as a means of collecting the data through a classroom action research. The procedures included planning, implementing, observing and reflecting. The results showed that teaching speaking using Role Play in Video Modelled Conversations could successfully improve students motivation in speaking. They find this technology can enhance their English learning motivation and effectively boost their English speaking ability. Keywords : motivation, Role Play, Video Modelled Conversation, framework. Abstrak : Role Play didalam Video Modelled Conversation dirancang dalam pengajaran speaking bukan saja karena bentuknya yang menarik tetapi juga karena fitur-fiturnya yang menggugah sebagai multimedia untuk meningkatkan motivasi siswa dalam berbicara. Studi ini bertujuan untuk menyelidiki motivasi siswa dengan menggunakan kerangka motivasi belajar bahasa yang dikembangkan oleh Dornyei. Angket dan wawancara cara semi terstruktur juga digunakan sebagai instrumen untuk pengumpulan data melalui penelitian tindakan kelas. Prosedur penelitian meliputi : perencanaan, pelaksanaan, pengamatan dan refleksi. Hasilnya menunjukkan bahwa pengajaran speaking menggunakan Role Play dalam Video Modelled Conversation telah berhasil meningkatkan motivasi siswa dalam berbicara. Mereka menemukan bahwa teknologi ini dapat memacu motivasi belajar bahasa Inggris dan secara efektif meningkatkan keterampilan bahasa Inggris mereka. Kata Kunci : motivasi, bermain peran, percakapan penutur asli di video, kerangka.